No modification in blood lipoprotein concentration but changes in body composition after 4 weeks of low carbohydrate diet (LCD) followed by 7 days of carbohydrate loading in basketball players - Michalczyk, M.; Zajac, A.; Mikolajec, K.; Zydek, G.; Langfort, J. (Journal of Human Kinetics, 2018)
Recently, low carbohydrate diets have become very popular due to their numerous health benefits. Unfortunately, little is known about their chronic effects on the blood lipid profile and other cardiovascular disease risk factors in athletic populations. We compared the results of a four week, well-planned low carbohydrate diet (LCD) followed by seven days of carbohydrate loading (Carbo-L) on fasting lipids - triacylglycerol`s (TAG), LDL-C, HDL-C, total cholesterol (TCh), glucose, insulin and HOMA-IR levels in 11 competitive basketball players. During the experiment, we also measured body mass (BM) and body composition changes: body fat (BF), % of body fat (PBF), and fat free mass (FFM). Both diet procedures significantly changed the fasting serum concentration of TAG (p < 0.05) and body fat content (kg and %) (p < 0.05), without negative changes in FFM. The Carbo-L procedure increased (p < 0.05) fasting glucose levels significantly. A LCD may be suggested for athletes who want to reduce body mass and fat content without compromising muscle mass. Several weeks on a LCD does not change the lipoprotein - LDL-C and HDL-C level significantly, while a seven-day Carb-L procedure may increase body fat content and fasting glucose concentration. Such dietary procedures are recommended for team sport athletes to reduce fat mass, lipid profile disorders and insulin resistance.